Uncertainty about the risks associated with microplastics among lay and topic-experienced respondents - Christina J. Thiele (Nature Portfolio, 2021)
Abstract Microplastics are contaminants of emerging concern but there is currently a lack of evidence on actual risks relating to them, despite claims in media and scientific articles. Research on people’s perceptions on microplastics is in its infancy. Here we present part of a larger survey about people’s perceptions of issues with microplastics. Our analysis of 1681 responses across the globe to an online questionnaire demonstrates a certain level of uncertainty, not only in lay people but also respondents who study/work on the topic of plastics and microplastics as a pollutant. This uncertainty ranges from level of concern about microplastics as an environmental issue to existing evidence for effects. Further, there is some discrepancy between risk perception and state of the research. Some of this may be driven by scientific work with some serious limitations in reporting and methods. This highlights the need for fact-checking of circulating information about microplastics, but also for addressing the discordance between ecotoxicological risk and how risk is framed within the scientific community.